Diversity and distribution of vetiver grass (Chrysopogan zizanioides (L) Roberty) and its manifold uses: A review: Diversity & uses of vetiver grass - Pandey, Ankit; Tiwari, S C (Journal of Spices and Aromatic Crops, 2023)
During the last few decades essential oils derived from different herbs and aromatic plants have received a growing focus of scientific investigation due to their multifunctional uses beyond their traditional roles as food additives and scents. Over 3000 species have been identified as medicinal plants that produce essential oils. Vetiver grass has wide range of diversity throughout the world with diverse genotype variability. It has multifarious uses in various agricultural, medicinal, aromatic, engineering, conservational and in industrial sector. The C. zizanioides is well known in various regions of South Asia, Southeast Asia, and West Africa. Vetiver roots, particularly those from Karnataka, have been utilised to make herbal drinks that are energising to combat tiredness. The vetiver grass, referred as "vetiver" or "vetiver–vetiver" in India, serves a variety of purposes in aromatic, pharmaceuticals, food, and beverage industries. This paper presents a review of the diversity & distribution of this crop along with its various uses and applications.